Right Ventricular Wall Hematoma Secondary to Percutaneous Coronary Intervention - Lee, Yong Whan (Korean Society of Echocardiography, 2009)
Intramyocardial hematoma is known to be associated with myocardial infarction, chest trauma, coronary artery bypass operation, and complication of percutaneous coronary intervention (PCI). We describe here a rare case of 50-year-old man with a huge right ventricular (RV) wall hematoma which was newly developed two hours after PCI. The patient was treated conservatively with a successful outcome. We discuss plausible mechanisms for the development of RV wall hematoma and treatment options for the case.